2016
DOI: 10.18533/ijbsr.v6i6.948
|View full text |Cite
|
Sign up to set email alerts
|

Creative Accounting Practices at Satyam Computers Limited: A Case Study of India’s Enron

Abstract: <p>Satyam Computers were once the crown jewel of Indian IT industry, however, the debacle of Satyam raised a debate about the role of CEO in driving a company to the heights of success and its relation with the board members and core committees. The scam brought to the light the role of corporate governance (CG) in shaping the protocols related to the working of audit committees and duties of board members. The Satyam scam was a jolt to the market, especially to Satyam stockholders.  This paper attempts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
53
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 20 publications
0
53
0
6
Order By: Relevance
“…Fraud is a problematic phenomenon in the world which has a lot of effects to economic sectors (Bhasin, 2013). A survey from PriceWaterhouseCoopers in 2009 revealed that 30% of all of the companies had faced criminalization economic in past 12 months with a huge loss in business activity (Gullkvist and Jokipii, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Fraud is a problematic phenomenon in the world which has a lot of effects to economic sectors (Bhasin, 2013). A survey from PriceWaterhouseCoopers in 2009 revealed that 30% of all of the companies had faced criminalization economic in past 12 months with a huge loss in business activity (Gullkvist and Jokipii, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that the investors' trust and confidence come along with the presence of independent and qualified audit committee (Leung, Richardson, & Jaggi, 2014). In addition, the financial frauds occur due to the small number of independent audit committee (Bhasin, 2013) and the minimum number of audit committee meeting (Yunos, Ahmad, & Sulaiman, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…(Bhasin, 2013;Sen et al, 2014) as well as abroad such as Enron Corporation, Global Crossing, WorldCom, Adelphia, Tyco etc. (Bhasin, 2013;Hogan et al, 2008;Pathak & Wells, 2008) where frauds were committed and investors cheated. These frauds were such that they were not identified from financial statements at the time.…”
mentioning
confidence: 99%
“…These frauds were such that they were not identified from financial statements at the time. Emphasizing the need for an independent audit committee, Bhasin (2013) asserted that one of the factors contributing to the Satyam fraud was weak independent directors and audit committee. Had audit committee comprised greater number of independent directors, the financial accounts might not have been manipulated for so long.…”
mentioning
confidence: 99%